PENGENDALIAN HAYATI PENYAKIT DARAH PADA PISANG DENGAN PSEUDOMONAD FLUORESEN DAN Bacillus spp. - Nur Edy (Universitas Tadulako, 2011)
Four antagonist bacterial strains, Pseudomonad fluorescent strain UTD1 (Pf-UTD1), Pseudomonad fluorescent strain UTD2 (Pf-UTD2), Bacillusspp. strain UTD1 (Ba-UTD2), and Bacillusspp. strain UTD1 (Ba-UTD1) which had been found to have biocontrol activity in vitro assays against blood disease bacteria, the causal agent of wilt banana, were tested for their compatibility in vitro and its antagonism in screen house using banana budless Kepok as test plant. The compatibility test showed that Pseudomonad fluorescent strain UTD1 was only compatible with Pseudomonad fluorescent strain UTD2, Pseudomonad fluorescent strain UTD2 compatible with all antagonist (Pf-UTD1, Ba-UTD1, dan Ba-UTD2), Bacillus spp. strain UTD1 only compatible with Bacillus spp. strain UTD2, and Bacillus spp. strain UTD2 compatible with all antagonist (Pf-UTD1, Pf-UTD2 and Ba-UTD1). Inoculation with blood disease bacteria caused significant wilting, and reduced plant growth. Single Inoculation using either Pseudomonad fluorescent UTD1 or Bacillus spp. UTD2 causing greater results with no wilting. Combination between Pseudomonad fluorescent UTD2 and Bacillus spp. UTD2 also showed no wilting. Generally, all treatments were considered good because they could reduce disease intensity less than 25%, except for Pseudomonad fluorescent UTD2 and Bacillus spp. UTD treatments which caused wilting up to 38.89%. The results suggested that both single and combination treatments of Pseudomonad fluorescent UTD2 and Bacillus spp. UTD2 can be used to control blood disease bacteria in wider scale. Key words: Bacillus spp., biological control, blood disease bacteria, pseudomonad fluorescent.